First records of Tumerozetidae and Nodocepheidae from Australia, with descriptions of new taxa and a re-assessment of the Polypterozetoidea (Oribatida, Brachypylina) - Colloff, Matthew J. (Zootaxa, 2022)
New species and a new genus of polypterozetoid oribatid mite are described from wet habitats in forests in south-eastern Australia: Tumerozetes roughleyi sp. nov. (Tumerozetidae), Nodocepheus luxtoni sp. nov. and Sacculella yarra gen. et sp. nov. (Nodocepheidae). The superfamily Polypterozetoidea has not been recorded previously from Australia. Tumerozetes roughleyi sp. nov. and Sacculella yarra gen. et sp. nov. were recorded from temperate Nothofagus cunninghami rainforest in central Victoria. Nodocepheus luxtoni sp. nov. was recorded from temperate rainforest in Tasmania and eastern Victoria. Tumerozetes was known previously only from New Zealand, and Nodocepheus from New Zealand, southern Africa and south-central America. The definitions of Tumerozetidae and Nodocepheidae are revised in the light of observations on the morphology of these new species, and their phylogenetic and biogeographical affinities with other members of the Polypterozetoidea are considered.